School-Based Mental Health Literacy Interventions in Guidance and Counseling Services: Ecological Determinants, Barriers, and Outcomes - Tika Mustikawati; Sunardi Sunardi; Eka Budhi Santosa (Universitas Hamzanwadi, 2026)
The numerous cases of adolescent mental health disorders that go undetected and are poorly handled are currently an urgent issue in education. This study aims to examine the urgency of improving students' mental health literacy through counselling services at SMP Negeri 20 Surakarta, while identifying main constraints in its implementation. The research method uses a qualitative descriptive approach, collecting data through direct observation and in-depth interviews with Guidance and Counselling teachers focusing on seventh-grade students. Data analysis is conducted using the Miles and Huberman interactive model, which includes three steps: data reduction, data display, and drawing conclusions. The results show that mental health literacy education at SMP Negeri 20 Surakarta remains minimal, unprogrammed, and lacks adequate learning resources. This condition is worsened by psychological barriers where students prefer to internalise their emotional problems rather than consult. The combination of limited programs and students' closed attitudes causes school mental health handling to be less effective. This study concludes that the services provided by BK teachers are not yet optimal due to the absence of standard literacy guidelines. Consequently, the school requires changes toward a more open, adolescent-friendly counselling system, with full support from school management and parents.